Moderating Environmental Uncertainty: Management Accounting Systems and Decentralization on Managerial Performance - Mursalam Salim (Faculty of Economics and Business, Universitas Warmadewa, 2024)
Competition in the world of business and industry requires company managers to organize organizational systems to make them more effective and efficient. The management and decentralized accounting system implemented by the company as well as uncertain environmental conditions also have an impact on the company. This research aims to analyze the influence of management accounting systems, decentralization, and environmental uncertainty on managerial performance. The population in this research are managers at telecommunications companies in the Papua region. The sampling in this research was a non-probability sampling design with a quota sampling technique obtained using an instrument in the form of 34 questionnaires which were distributed directly. The data analysis method in this research uses Structural Equation Model (SEM)-PLS analysis. The research results show that decentralization can influence managerial performance, but the management accounting system implemented is not able to provide a significant influence on managerial performance. Meanwhile, conditions of environmental uncertainty as a moderating variable are also unable to influence the relationship between decentralization and management accounting systems on managerial performance.